Managing depressive disorders (Adis international, 2000)
Looks at the many facets of depressive disorders. Reviews how interventions and outcomes may be optimized. Covers areas such as dysthymia, double depression, recurrent brief depression, seasonal affective disorder and psychotic depression. Looks at depression in the elderly and among children. For psychologists and psychiatrists.